Comparative proteomic analysis of sulfur-oxidizing Acidithiobacillus ferrooxidans CCM 4253 cultures having lost the ability to couple anaerobic elemental sulfur oxidation with ferric iron reduction - Kucera, Jiri; Sedo, Ondrej; Potesil, David; Janiczek, Oldrich; Zdrahal, Zbynek; Mandl, Martin (Research in microbiology, 2016)
In extremely acidic environments, ferric iron can be a thermodynamically favorable electron acceptor during elemental sulfur oxidation by some Acidithiobacillus spp. under anoxic conditions. Quantitative 2D-PAGE proteomic analysis of a resting cell suspension of a sulfur-grown Acidithiobacillus ferrooxidans CCM 4253 subculture that had lost its iron-reducing activity revealed 147 protein spots that were downregulated relative to an iron-reducing resting cell suspension of the antecedent sulfur-oxidizing culture and 111 that were upregulated. Tandem mass spectrometric analysis of strongly downregulated spots identified several physiologically important proteins that apparently play roles in ferrous iron oxidation, including the outer membrane cytochrome Cyc2 and rusticyanin. Other strongly repressed proteins were associated with sulfur metabolism, including heterodisulfide reductase, thiosulfate:quinone oxidoreductase and sulfide:quinone reductase. Transcript-level analyses revealed additional downregulation of other respiratory genes. Components of the iron-oxidizing system thus apparently play central roles in anaerobic sulfur oxidation coupled with ferric iron reduction in the studied microbial strain.
Keywords: mutace; 2D gelová elektroforéza; proteom; železo; Tandem Mass Spectrometry; bakteriální proteiny; Acidithiobacillus ferrooxidans; Proteome; Bacterial Proteins; síra; Mutation; stanovení celkové genové exprese; Proteomics; oxidace-redukce; tandemová hmotnostní spektrometrie; Oxidation-Reduction; Iron; Anaerobic respiratory pathway; Electrophoresis, Gel, Two-Dimensional; Sulfur metabolism; Anaerobiosis; anaerobióza; Ferric iron reduction; Gene Expression Profiling; Acidithiobacillus; Sulfur